SISTEM INFORMASI PENJUALAN AIR MINERAL TRIPANCA PADA TOKO RUDI KECAMATAN BARADATU KABUPATEN WAY KANAN - Dessy Permata Sari; Deka Mario; Sidik Rahmatullah; Bayu Maftoha; Siti Amnah (Jurnal Cendikia, 2025)
The advancement of information technology has significantly transformed various aspects of businessoperations, including the small and medium enterprises (SMEs) sector. The implementation of computerizedinformation systems has become a strategic solution to enhance efficiency, accuracy, and speed in businessprocesses. Toko Rudi, a business engaged in the sales of Tripanca mineral water in Baradatu District, WayKanan Regency, still relies on manual systems for transaction recording, inventory management, and salesreporting. This manual approach has led to several challenges, such as transaction delays, a h igh risk of humanerror in data recording, and difficulties in real-time data monitoring. This study aims to design and implement aSales Information System to address these issues and improve operational performance.The system development methodology applied in this research is Extreme Programming (XP), known for itsiterative approach and flexibility in accommodating changing user requirements. The stages include planning,system design using Unified Modeling Language (UML), coding with NetBeans IDE 8.0 and MySQL, andcomprehensive system testing. Data collection was conducted through direct interviews with the owner and staff,observation of operational processes, and literature review related to information system concepts andsupporting technologies.The implementation results demonstrate that the developed information system successfully automates the entiretransaction process, customer data management, mineral water inventory control, and the generation ofaccurate and timely sales reports. The system significantly improves operational efficiency, reduces humanerror, and facilitates data-driven decision-making. Furthermore, the user-friendly interface ensures that userscan quickly adapt to the new system without requiring extensive training.In conclusion, the implementation of the sales information system at Toko Rudi has had a positive andsignificant impact on operational effectiveness. This system can serve as a reference model for other SMEsseeking to adopt information technology to support sustainable business growth and competitiveness in thedigital era.